Incidence Rate and Risk Factors of Radial Artery Spasm during Transradial Coronary Angiography - Pishgahi, Mehdi; Mehrabi, Mohammad Ali; Adeli, Mobina (Archives of Men’s Health, 2023)
Background: Radial artery spasm (RAS) is one of the most common complications of radial coronary angiography. Several demographic and clinical factors increase the risk of RAS in this procedure. We aimed to evaluate the effect of various risk factors on the incidence and severity of RAS in radial coronary angiography. Methods: This cross-sectional study was performed on 120 patients who were randomly selected from candidates referred to Shahid Modarres Educational Medical Center for coronary angiography by the radial method. After angiography, radial arteriography was performed to diagnose spasms. The association of some demographic and clinical factors with the incidence and severity of RAS was evaluated. Results: 35 of the 120 patients (29.16%) developed RAS during angiography. Shorter height, shorter radius bone length, less radial artery diameter, longer procedure length, diabetes mellitus, more catheters used, and female sex were significantly associated with higher incidence. The predictive power of these factors for the occurrence of spasms was very good with AUC=0.88. Age, shorter height, higher body mass index, smaller radial artery diameter, longer procedure time, diabetes mellitus, failure of initial effort for puncture, number of catheters used, and female sex were significantly associated with the severity of spasms. Conclusions: The incidence or severity of spasms during the procedure can be reduced by examining the available risk factors for every patient before deciding to perform angiography.